Interview 1 - Abubakari, Yushawu
This file contains the interview notes with Don Bee. Don Bee (pseudonymize) is 26 years old and has been in the scamming industry for 6 years. Don Bee has 4 scammers who are under his training and 2 people who he calls his bosses. Bon bee is married with two kids and lives in his own house. Interview was conducted in Don Bee’s house on two occasions.